PENGARUH PROMOSI JABATAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN (Studi Pada PT. Polowijo Gosari Gresik ) - Nur Atika Zuchrufillah; Abdul Qodir Djaelani; Achmad Agus Priyono (E-JRM : Elektronik Jurnal Riset Manajemen, 2018)
AbstractThe study aims is to determine the effect of promotion and compensasion toemployees performance. The sample in this study amounted to 104 respondentsemployees of PT. Polowijo Gosari Gresik. Method data analysis used isquantitative analysis by using test descriptive statistics, normality test, classicalassumption test, linear regression analysis multiple and hypothesis testing.The results of this study showed that the effects of promotion andcompensasion to employees performance at PT. Polowijo Gosari Gresikpartially effect on the performance of employees at PT. Polowijo GosariGresikKeyword: employees performance, promotion, compensation